Analisis Deformasi Jalan Penghubung Antara Kelurahan Sanga-Sanga Dalam dan Kelurahan Pendingin Tahun 2015 dan 2021 Menggunakan Metode Interferometry Synthetic Aperture Radar - Taufan Yanuar Muslim; Nia Kurniadin; Dyah Widyasasi; Romansah Wumu (Journal of Geomatics Engineering, Technology, and Science, 2023)
The rise of coal mining in the East Kalimantan area which is close to public road access is thought to affect the quality and sustainability of surrounding public road access. The aim of this research is to determine the use of remote sensing data to analyze land subsidence or deformation that occurs on the connecting road between Sanga-Sanga Dalam Village and Pendingin Village, Sanga-Sanga District, Kutai Kartanegara Regency. The method used in this research is quantitative descriptive, namely determining ground deformation on roads obtained by analyzing Sentinel-1 imagery in 2015 and Sentinel-1 imagery in 2021. Ground deformation can be identified using a satellite-based remote sensing method through interferometry of two SAR images (interferometry synthetic aperture radar or InSAR) uses the Sentinel application platform (SNAP) which is an open source software (FOSS) application. Interferometry can represent changes in the line of sight between the ground and satellites in general. Changes in line of sight can be interpreted as signals of ground deformation. The results of this research can provide adequate information regarding comparative data on land elevation on the Sanga-Sanga Dalam - Pendingin road from several points experiencing land subsidence or deformation on average of 161.3 cm with an average land subsidence rate of 23.04 cm/year . Thus, remote sensing technology using the InSAR technique can be used to determine changes that occur in a short time and at low cost.